This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Exercises 4.5 and a general solution is y ( t ) = y p ( t ) + y h ( t ) = t 2 4 t + 7 e t 4 + c 1 e t + c 2 te t . Next, we satisfy the initial conditions. 0 = y (0) = 7 1 / 4 + c 1 2 = y (0) = 4 1 / 4 c 1 + c 2 c 1 = 27 / 4 c 2 = 25 / 4 + c 1 = 1 / 2 . Therefore, the solution to the given initial value problem is y ( t ) = t 2 4 t + 7 e t 4 27 e t 4 te t 2 . 32. For the nonhomogeneous term, e 2 t + te 2 t + t 2 e 2 t = ( 1 + t + t 2 ) e 2 t , a particular solution has the form y p ( t ) = t s ( A + A 1 t + A 2 t 2 ) e 2 t . Since r = 2 is not a root of the auxiliary equation, r 2 1 = 0, we choose s = 0. 34. Neither r = i nor r = 2 i is a root of the auxiliary equation, which is r 2 + 5 r + 6 = 0. Thus, by the superposition principle, y p ( t ) = A cos t + B sin t + C cos 2 t + D sin 2 t. 36. Since the auxiliary equation, r 2 4 r + 4 = ( r 2) 2 = 0 has a double root r = 2 and the nonhomogeneous term can be written as t 2 e 2 t e 2 t = ( t 2 1 ) e 2 t , a particular solution to the given equation has the form y p ( t ) = t 2 ( A 2 t 2 + A 1 t + A ) e 2 t . 38. Since, by inspection, r = i is not a root of the auxiliary equation, which is r 4 5 r 2 +4 = 0, we look for a particular solution of the form y p ( t ) = A cos t + B sin t. 131 Chapter 4 Differentiating y p ( t ) four times, we get y p ( t ) = A sin t + B cos t, y 00 p ( t ) = A cos t B sin t, y 000 p ( t ) = A sin t B cos t, y (4) p ( t ) = A cos t + B sin t....
View
Full
Document
This note was uploaded on 02/12/2011 for the course MA 221 taught by Professor Mazmani during the Spring '08 term at Stevens.
 Spring '08
 MAZMANI
 Equations

Click to edit the document details